2007
DOI: 10.1007/s11896-007-9000-9
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Offender Profiling: A Systematic Review of the Profiling Literature Published Over the Past Three Decades

Abstract: Despite the immense popularity of offender profiling as both a topic of fascination for the general public as well as an academic field of study, concerns have been raised about the development of this area of scientific inquiry. The present study provides a preliminary step towards moving the field forward as it reviews the type and quality of studies dealing with offender profiling over the past 31 years. Based on a content analysis of 132 published articles, the review indicates that researchers investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 95 publications
1
45
0
1
Order By: Relevance
“…Conversely, it may be that in acknowledging these other profiling methods, they run the risk of "making them real," thereby validating any claims other authors make against their own paradigms. A short list of research suffering from this includes Dowden, Bennell, and Bloomfield (2007); Godwin (2002); Canter (2000); and Napier and Baker (2005). 3 3� More research needs to be conducted in the area of metacognition in criminal profiling.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it may be that in acknowledging these other profiling methods, they run the risk of "making them real," thereby validating any claims other authors make against their own paradigms. A short list of research suffering from this includes Dowden, Bennell, and Bloomfield (2007); Godwin (2002); Canter (2000); and Napier and Baker (2005). 3 3� More research needs to be conducted in the area of metacognition in criminal profiling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Goodwill et al found that in examining the association between crime scene behaviours and offender characteristics, both thematic and typological approaches were inferior to multivariate statistical approaches. Although somewhat limited in the past, the use of advanced multivariate statistics is now prominent in the offender profiling literature as evidenced by a marked increase in recent quantitative research articles (Dowden, Bennell, & Bloomfield, ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the profi ling literature over the past 30 years shows that most papers have been published between 1996 and 2005 (Dowden, Bennell,were published during this 9-year period. Interestingly, rape was the second specifi c type of crime investigated, just behind homicide (Dowden, Bennell, & Bloomfi eld, 2007).…”
Section: Introductionmentioning
confidence: 99%